Robustness analysis of beamforming based designs for mmWave Full-Duplex Amplify-and-Forward relays - R. López-Valcarce; M. Martínez-Cotelo (2020 14th International Conference on Signal Processing and Communication Systems (ICSPCS), 2020)
We consider the robust design of a millimeter wave MIMO two-hop system in which source, relay and destination are equipped with large antenna arrays. The relay implements the amplify-and-forward protocol and operates in full-duplex mode, thus being subjected to self-interference (SI). Imperfect channel state information (CSI) is assumed in all involved links, including the SI channel, with a deterministic isotropic bounded model on CSI errors. The proposed robust design seeks to maximize the worst-case spectral efficiency, accommodates both digital and phase shifter-based analog beamforming, and is computationally simple; moreover, it does not require knowledge of the size of the CSI uncertainty regions.
Keywords: full-duplex; mmWave; rodin